1997
DOI: 10.4213/tvp1955
|View full text |Cite
|
Sign up to set email alerts
|

Closedness of sum spaces and the generalized Schrödinger problem

Abstract: Установлены некоторые общие свойства замкнутости сумм про странств измеримых функций. В качестве применения доказаны су ществование и единственность решений обобщенной задачи Шредин-гера при некотором условии интегрируемости, но без каких-либо предположений о топологии или ограниченности. Полученные свой ства позволяют также доказать интересный результат о структуре законов с многомерными частными распределениями, установить су ществование оптимальных аппроксимаций в аддитивных статисти ческих моделях и обобщи… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Note that equation 4.1 is known in the mathematical physics literature as the Schrödinger-Bernstein equation, cf. Rüschendorf and Thomsen (1998)…”
Section: F Connections To Statistical Physicsmentioning
confidence: 99%
“…Note that equation 4.1 is known in the mathematical physics literature as the Schrödinger-Bernstein equation, cf. Rüschendorf and Thomsen (1998)…”
Section: F Connections To Statistical Physicsmentioning
confidence: 99%
“…This problem has a long history (e.g., Beurling [9]). A series of results revealed that the additive form f (x) + g(y) always holds, but also that the measurability of (f, g) fails without additional conditions; moreover, even when measurability holds, integrability fails without further conditions (see Borwein and Lewis [11], Csiszár [14], Föllmer and Gantert [23], Rüschendorf and Thomsen [49,50]). The study of Schrödinger potentials remains an area of active study (see for instance Altschuler et al [2], Deligiannidis et al [20], Gigli and Tamanini [27], Nutz and Wiesel [43,44]) that we have benefited from, especially for our companion paper [45].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Remarkably, we have not been able to use the classical arguments of mathematical finance, nor the techniques known from the dual problem of martingale optimal transport [7] in this work, despite the setting lying between those two. Instead, we draw inspiration from the literature on the dual of the Schrödinger bridge problem, especially [11,50]. See also [39,42] for general introductions.…”
Section: Introductionmentioning
confidence: 99%